1987
DOI: 10.1111/j.1472-8206.1987.tb00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Zopiclone, Triazolam and Placebo on Memory and Psychomotor Performance in Healthy Volunteers

Abstract: This study evaluated the effects of acute doses of zopiclone (7.5 mg), triazolam (0.25 mg) and placebo on memory and psychomotor performance of 12 normal volunteers. The subjects received both drugs in a repeated measure, double-blind Latin square design. The tests (CFF, CRT, DSST, memory assessments) were performed before and 2 and 6 hr after treatment. Zopiclone and triazolam induced an anterograde amnesia affecting short-term and long-term memory which lasted less than 6 hr. No retrograde amnesia was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 18 publications
4
32
1
Order By: Relevance
“…Previous studies have shown them in volunteers who were tested 4±6 h after 7 . 5 mg doses (Subhan and Hindmarch, 1984;Griths et al, 1986;Warot et al, 1987). To our knowledge, however, only one other study has previously found that these eects persist for as long as 11 h (Fossen et al, 1983).…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have shown them in volunteers who were tested 4±6 h after 7 . 5 mg doses (Subhan and Hindmarch, 1984;Griths et al, 1986;Warot et al, 1987). To our knowledge, however, only one other study has previously found that these eects persist for as long as 11 h (Fossen et al, 1983).…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, zopiclone presents affinity not only for the w1 subtype receptors but also for the w2 subtype, underlying its anxiolytic properties in humans [15,16] and anticonvulsant, myorelaxant and anxiolytic properties in animals [17]. Thus, zopiclone induces memory disorders to the same extent as benzodiazepines [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Choice reaction time seems to be sensitive to the effects of benzodiazepines under the same types of conditions seen with simple reaction time tests. Those studies that evaluate the effects of a benzodiazepine within the time frame of the half-life of a therapeutic dose of the parent compound typically detect impairment with these tests (Nikaido & Ellinwood, 1987;Preston et al, 1988;Roache & Griffiths, 1987;Seppala et al, 1976;Subhan et al, 1986;Warot et al, 1987). In a study by Schaffler & Klausnitzer (1989) impairment was noted with a subchronic dose of bromazepam over a 7 day period but in a study by Preston et al (1988) subtherapeutic doses of lorazepam did not impair choice reaction time performance.…”
Section: Reaction Timementioning
confidence: 99%
“…In these studies the measure was when flicker was detected in a light whose sinusoidal fluctuation was initially set at a level at which a steady light was perceived instead of measuring when a flickering light appeared steady. Using this variation decreased CNS activity was measured over an 8 h period for 0.25 mg triazolam in contrast to the 2 h period of observed impairment on the more traditional version of the test (Warot et al, 1987). The CFFT appears to be quite sensitive to the CNS depression associated with the use of benzodiazepines and can readily be incorporated into a computerbased testing battery.…”
Section: Critical Flicker Fusion Thresholdmentioning
confidence: 99%
See 1 more Smart Citation